Handbook of frozen foods - Hui, Y.H. (Marcel Dekker, 2011)
Handbook of Frozen Foods describes the manufacture, processing, inspection, and safety of frozen foods. It surveys a range of topics in frozen food packaging, quality, and shelf-life from more than 50 of the most respected leaders in the field. The book describes the procedures, regulations, and technologies impacting each category of frozen food production, from red meat, poultry, and eggs to fruit, vegetables, dairy, and bakery products. Outlining procedures before and after freezing that optimize the quality and texture of frozen foods, the book discusses practical guidelines to ensure the safety and reduce their deterioration of frozen food products.